Analysis of ovarian cancer immune cell profile identifies immunosuppressive states associated with adverse clinical attributes and survival times - Ana Moscoso; Navid Mohammad Mirzaei; Leili Shahriyari (PLoS ONE, 2026)
The ovarian tumor microenvironment (TME) is highly immunosuppressive, limiting immunotherapy effectiveness. We investigated whether the composition, ratios, and polarization of infiltrating immune cells provide prognostic value in ovarian cancer (OC). Our analysis revealed that immune ratios, including CD8/Treg and CD8/CD4, were more predictive of survival than absolute CD8 + , CD4 + , or Treg levels. Prior studies have reported associations between higher CD8/Treg ratios and improved responses to immune checkpoint inhibitors, highlighting the importance of effector–regulator balance; however, immunotherapy response was not evaluated in this cohort. Additionally, macrophage polarization proved to be crucial: pro-tumor M2-macrophages were associated with vascular invasion, persistent tumor, and worse survival, while higher naïve M0-macrophage levels predicted improved outcomes. Surprisingly, anti-tumor M1-macrophages lacked prognostic significance, suggesting possible benefits in preserving an M0-macrophage pool. Neutrophil infiltration, though relatively uncommon, correlated with poor survival, supporting reports that neutrophils suppress T-cell responses. Immune infiltration was linked to aggressive features such as vascular invasion, reflecting both heightened recognition and compensatory recruitment of suppressive populations. Unsupervised clustering identified four immune-defined subtypes, with worse survival in clusters enriched for M2-macrophages and CD4 + T-cells and depleted in M0-macrophages, particularly in advanced disease. Overall, our findings highlight the prognostic value of immune ratios, macrophage polarization, and neutrophil activity in OC, suggesting new avenues for risk stratification and future therapeutic investigation.